A joint shear model incorporating small-scale and large-scale irregularities. (June 2015) - Oh, J.; Cording, E.J.; Moon, T.
Abstract: The strength and dilation of rock joints in the field cannot be evaluated solely on the basis of parameters scaled from laboratory data, but also requires assessment of large-scale irregularities not present in the laboratory sample. A constitutive model for rock joints has been developed that considers the dilation and strength along both small-scale joint roughness scaled from laboratory data, and large-scale waviness determined from geologic observations. The model's performance is illustrated by providing its correlation with experimental results taken from literature. The degradation in dilation and post-peak strength along small-scale irregularities is modeled using the plastic work done in shear, and the degradation along large-scale irregularities is modeled using a sinusoidal function. A dimensionless product of plastic work, rock strength, and wavelength of irregularities has been developed which fits the direct shear test results. An approach to scaling shear strength and shear displacement from laboratory to field-scale is also suggested. Highlights: The strength of rock joints in the field cannot be evaluated solely from lab-tests. It requires assessment of large-scale irregularities not present in the lab sample. We developed a joint model incorporating small and large-scale irregularities. Plastic work is used to model the strength degradation of small irregularities. Sinusoidal function is used for the degradation of large irregularities.